Effectiveness of Child-Friendly Schools Based on the CIRC Method toward Learning Outcomes in Arabic Language Education at MI Tarbiyah Islamiyah Palembang - Taqwatul Karimah; Mukmin; Nurul Hidayah; Yusnida; Muhammad Ferdy Pratama; Ahmad Yani (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
The lack of reading references is one of the factors contributing to the low level of student interest in writing. Therefore, the CIRC method enables students to collaborate in small groups to assist one another by combining reading, writing, and discussion activities into a single learning activity. Where this is consistent with the fundamental values of a child-friendly school, which emphasizes the safety, comfort, health, friendliness, and enjoyment of children. The objective of this research is to investigate how Arabic language learning using the CIRC method can be adapted to the principles of child-friendly schools. This study uses the sequential explanatory method, also known as the mixed method, which in its implementation employs a one-group pre-test and post-test design, which means that only one experimental class is used, without a comparison class. The results show that this treatment can improve students' Arabic language skills as indicated by an average pre-test score of 35.33 and a post-test score of 80.67. This implies that students' proficiency in the Arabic language has improved. This learning can also provide motivation and facilitate developing of students' social skills. Through group study, students will acquire the ability to respect and appreciate one another, which is consistent with the values of a child-friendly, anti-discriminatory institution.